Consumo de ceftriaxona en el Hospital Víctor Lazarte Echegaray – Essalud, años 2006 - 2007 - Idrogo Tafur, Harry (2008)
This study is descriptive, retrospective cross whose aim was to determine the profile of ceftriaxone 1g consumption during the years 2006 and 2007 at the Hospital Lazarte Victor Echegaray. The results indicate that the service of Medicine is the largest consumer of ceftriaxone 1 g expressed DDD/100 beds in the day, had during the years 2006 and 2007, can also be observed that there was a lower consumption of ceftriaxone 1 g during the year 2007 in comparison with the year 2006. By making use of the graphical trend of consumption shows that the services of Medicine, Surgery, NICU are the biggest trend of consumption of ceftriaxone have in the future. When explained in graphic consumption of ceftriaxone 1 g (expressed in DDD/100 day) month by month, the UCI is the service of the highest consumption of ceftriaxone 1g during the month of September. And as the final links to obtain the annual expenditure of ceftriaxone 1 g, being the service of medicine which increased spending generously in the purchase of antibacterial Hospital Lazarte Victor Echegaray. You can also reveal what is the trend of annual expenditure on the purchase of antibacterials for the institution, with its tendency to decline in consumption in the different services